Integrated Software Tools for the OR/MS Classroom - Castillo, Ignacio; Lee, Tom; Pintér, János (Algorithmic Operations Research, 2008)
In recent years, a growing range of software technologies has been deployed in the classroom, as a component of business, engineering, and science curricula. These technologies enable a more direct, interactive student involvement in educational or research project development. Within this general framework, we see a strong case for using integrated scientific-technical computing systems. To illustrate this point, we review the key features of Maple, with an emphasis on its optimization model development and solver features. Maple is then used to formulate, solve, and visualize an optimization model example suitable for the classroom.